CFD comparison of friction and pressure drag road and time trial helmets for wheelchair racing - Forte, Pedro (2017)
Computer Fluid Dynamics has been used by sports scientists aiming to improve the athlete’s performance in sprinting events. In wheelchair sprinting, the athlete’s velocity can reach up to 7m/s. The use of sport garments such as helmets may reduce the aerodynamic drag by 10%. Therefore, the aim of this study was to compare the friction and pressure drag between road and time trial helmets. A wheelchair racer (category T-52), European medallist in sprinting events and world championships finalist was recruited for this research. The subject wore a road helmet (LAS, Istron) and a time-trial model (LAS, Cronometro). The geometries were obtained by a 3D scan (Artec-L, Artec Group, Inc., USA). Fluent (Fluent, Inc., USA, New York) code allowed to compute numerical simulations applying a mathematical model to the fluid flow, in a created domain with discretized expressions of the Navier-Stokes equations. It solves the equations with a finite volume approach. The domain, created by a 3D mesh of subdivided cells, represented the fluid flow around the head and helmets. Realizable k-epsilon turbulence model was applied. The 3D mesh had more than 6 million cells for booth helmets domains and helmets angles of attack was 0º. The fluid flow velocity was set in inlet portion of the dome surface at 2m/s, with increments of 1.5 m/s up to 6.5 m/s. Typically the wheelchair racer will reach these range of speeds over a short distance event. Pressure and friction drag increased with velocity